Comparison of hemoglobin and hematocrit levels at 1, 4 and 24 h after red blood cell transfusion - Krittadhee Karndumri (2019)
© 2019 Elsevier Ltd Previous studies have shown that equilibration following a red cell transfusion had occurred by 24 h. A shorter time to follow the hemoglobin (Hb) and hematocrit (Hct) after transfusion may help physicians to provide earlier and more pertinent treatment. This was a prospective study conducted from December 2014 to August 2015. This research aimed to determine the equilibration time point of the level of Hb and Hct after one unit red blood cell (RBC) transfusion. Patients were randomized into three groups and Hb level and Hct were assessed at one, four or 24 h after transfusion. The mean differences in Hb level and Hct before and after transfusion were compared between each group. Sixty patients were eligible for enrollment onto this study; 20 patients were therefore allocated to each group. The median age was 51 years old, male predominating (83.33%). The most common indication for transfusion was post-operative anemia (88.33%). There were no significant differences between the baseline characteristics baseline Hb, Hct and volume of RBC transfusion in each group. The mean differences in Hb (g/dl)/Hct (%) level at the different time points of one, four and 24 h were 1.21/3.62, 1.19/3.63, and 0.95/3.09 respectively (P = 0.109 and P = 0.398, respectively). The equilibration of Hb and Hct did not differ between one, four and 24 h after a RBC transfusion. The target Hb and Hct can be determined at one hour after transfusion.